Pengaruh Strategi Mind Mapping Terhadap Motivasi dan Prestasi Belajar Siswa Mata Pelajaran Fikih di Kelas VII MTsN 8 Gunungkidul - Ngadiyan Ngadiyan (Jurnal Pendidikan Madrasah, 2018)
This research is aimed to know: (1) the influence of mind mapping strategy towards the students achievement in the Fiqh subject in the seventh grade of MTsN 8 Gunungkidul, (2) the influence of mind mapping strategy towards the students motivation in Fiqh Subject in the seventh grade of MTs N 8 Gunungkidul, and (3) the influence of the students achievement towards the students motivation in the Fiqh subject in the seventh grade of MTs N 8 Gunungkidul. This research applied the quasy experiment method which followed by 72 students of MTs N 8 Gunungkidul that divided into two groups, experiment group and control group. In order to find out the data of the students’ achievement used the pretest and posttest and to find out data of the students’ motivation used the questionnaire of the student motivation with Likert scale. The data were analyzed by descriptive analysis, t-test, and simple regression using computer program of SPSS for windows 10,00 version. The result of the research showed that, first, there was the influence of mind mapping strategy towards the students’ achievement in Fiqih subject in the seventh grade of MTs N 8 Gunungkidul. Second, there was the influence of mind mapping strategy towards the students’ motivation in the Fiqh subject in the seventh grade of MTs N 8 Gunungkidul, and third, there was the influence of the students achievement towards the students motivation in the Fiqh subject in the seventh grade of MTs N 8 Gunungkidul.